2011
DOI: 10.1248/bpb.34.1613
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Geniposide on Metabolic Disease Status in Spontaneously Obese Type 2 Diabetic Mice and Free Fatty Acid-Treated HepG2 Cells

Abstract: Obesity, diabetes, hyperlipidemia and hypertension, which are caused by hypernutrition and lack of exercise, are often found in the same person. These symptoms used to be called "the deadly quartet," "Syndrome X" or "insulin resistance syndrome," but these names have recently been collectively replaced with "metabolic syndrome (MS)," since the presence of visceral fat accumulation-type obesity has been recognized as the major disease base. It should be noted that progression of MS increases the risk of future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 30 publications
0
78
0
1
Order By: Relevance
“…Geniposide is one of the active ingredients in traditional Chinese medicine used to fight obesity [35] . For instance, geniposide has been used for the amelioration of spontaneously obese type 2 diabetic mice and has been shown to suppress body weight and visceral fat accumulation [36] . Inflammatory cytokine release and neutrophil infiltration play an important role in colitis; MPO can indirectly reflect the vitality of neutrophil infiltration [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Geniposide is one of the active ingredients in traditional Chinese medicine used to fight obesity [35] . For instance, geniposide has been used for the amelioration of spontaneously obese type 2 diabetic mice and has been shown to suppress body weight and visceral fat accumulation [36] . Inflammatory cytokine release and neutrophil infiltration play an important role in colitis; MPO can indirectly reflect the vitality of neutrophil infiltration [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these data show that GNP has therapeutic benefits in patients with liver disease. Interestingly, another study showed that inhibition of UCP2 with GNP exacerbated palmitate-induced hepatic steatosis, which is controversial with previous study demonstrating decreased triacylglycerol concentrations [46], may be attributed to the low concentration (5 μM) and the compensatory effect of upregulated UCP2 expression.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 77%
“…This reducing effect might depend on geniposide, the main compound of Gardeniae Fructus. Geniposide had the effect on lowering the quantity of visceral fat and showed an alleviating effect on abnormal glucose/lipid metabolism [24]. The lowering effect of Gardeniae Fructus on serum triglyceride was parallel with its anti-hyperglycemic action.…”
Section: Discussionmentioning
confidence: 91%